EVALUATING THE EFFECTIVENESS OF NEGOTIATED PLANNING TOOLS: THE CASE OF THE LOMBARDY REGION - Marta Dell’Ovo; Marco Rossitti; Francesca Torrieri; Giulia Datola; Danny Casprini; Alessandra Oppio (Valori e Valutazioni)
Regional Law 19/2019 introduced new tools for Negotiated Planning (NP) in Lombardy, aimed at facilitating collaboration between public and private entities. This law introduces various instruments for coordinating public and private entities, such as the Framework Agreement for Territorial Development (Accordo Quadro di Sviluppo Territoriale - AQST), the Program Agreement (Accordo di Programma - AdP), the Simplified Local Agreement (Accordo Locale Semplificato - ALS) and the Agreement for Economic, Social, and Territorial Revitalization (Accordo di Rilancio Economico, Sociale e Territoriale - AREST). However, the assessment of regional interest and performance monitoring of NP proposals remain problematic due to the lack of transparent and replicable indicators. This research paper presents a multidimensional evaluation model, which introduces innovative criteria and indicators to evaluate NP proposals. With the support of multicriteria analysis as a reference evaluation methodology, the model relies on binary indicators to assess the programmatic, planning, territorial, environmental, social, economic-financial, employment and procedural coherence of the proposals. The application of the model to real case studies also makes it possible to test its effectiveness and improve the monitoring of NP instruments. The proposed model thus aims at improving the management and effectiveness of the NP instruments, offering a robust and replicable method for evaluation and monitoring.